Komunitas Berpagar: Antara Inovasi Sosial dan Ketegangan Sosial (Studi Kasus Komunitas Berpagar di Propinsi D.I Yogyakarta, Indonesia) - Widhyharto, Derajad S. (Jurnal Ilmu Sosial dan Ilmu Politik, 2009)
Gated communities grow fast in Yogyakarta, not only among middle-up class, but also middle-lower class in âkampungâ. Social dynamics of urban society have increased the complex social problems. Urban social problems such us criminality, has made urban dwellers anticipate it by putting extra security in their homes. Urban community tries to secure their homes and their circumstances by using several things, such as installing tall entrance gates surrounding their residential areas or paying more for security guards. This research is aimed at capturing how far social changes has emerged after this so-called âgated communityâ has rapidly grown in Indonesian society. Using the case of Yogyakarta city, this paper tries to describe the phenomenon of âgated communitiesâ into more comprehensive account.